Improving Students’ Class Participation by Optimizing The Use of Think-Pair-Share Technique - Burhanuddin Yusuf Alfino; Dewi Rochsantiningsih; Hefy Sulistyawati (PAEDAGOGIA, 2019)
An effective and successful language learning process can only be achieved when students actively participate in the class. This research aimed to improve students’ class participation by the optimization of  Think Pair Share (TPS) technique. This research was conducted as classroom action research whose subject was the tenth grade students of DPIB B class in a vocational highschool in Surakarta in the academic year of 2018/2019. The data were gathered from the research instruments, such as: observation, interview, questionnaire, research diary, and photographs. The data were analyzed using both quantitative and qualitative. The findings of the research showed that implementation of TPS was successful in improving students’ participation with the increase in the number of: (1) students asking and answering questions; (2) students’ interaction during the class; (3) students paying their attention during the class; (4) students interacting during group discussion; and (5) students speaking in front of the class. There were also some challenges that the researcher faced during the implementation of TPS technique, such as: (1) the familiarity of the technique to the students; (2) teacher’s control of the class; (3) students’ readiness in receiving the lesson; (4) difficulty in expressing opinion and ideas; (5) lack of confidence in speaking; (6) low grammar mastery; and (7) lack of vocabulary.